Hubungan Helicopter Parenting dengan Academic Adjustment Pada Mahasiswa Semester 2 - Ayuningtyas, Annisa Sari; Trihandayani, Dewi (Innovative: Journal Of Social Science Research, 2024)
The university is an environment with all the academic demands that students will face. Therefore, it is hoped that students can adapt well to academic life at university. Academic adjustment or adjustment is a student's ability to adapt himself to the academic demands that exist in his environment. Adjustments are academically important to make because they are used in the lecture aspect. Academic adjustment can be influenced by parenting patterns. Helicopter parenting can influence academic adjustment because this parenting style specifically focuses on academics and competitiveness in the future because that way the child will achieve success in the future. This research was conducted to determine the analysis of the relationship between helicopter parenting and academic adjustment in second semester students. The method used was a quantitative approach with correlation via SPSS version 25. The measuring tool used was the Helicopter Parenting Instrument (HPI) developed by Odenweller et all (2014) to measure helicopter parenting and the Academic Adjustsment Scale (AAS) developed by Anderson et all (2016) to measure individual academic adjustment. Respondents in this study totaled 150 participants, consisting of 42 men and 108 women aged 18-23 years. The results of the research that has been carried out show that the Helicopter Parenting Instrument (HPI) and Academic Adjustment Scale (AAS) measuring instruments are reliable, and the results of the correlation test show a significance of 0.503 (p<0.05), which means there is a relationship between helicopter parenting and academic adjustment